Direction of Trade Statistics Yearbook, 2006. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2006)
The Direction of Trade Statistics yearbook gives seven years of data for about 184 countries and two sets of world and area summaries: world and area trade as seen by the reporting countries and as seen by the partner countries to those transactions. The yearbook is usually published in September.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: General Financial Markets; Investment Decisions; Portfolio Choice